School Management Strategies to Address Low Student Interest in STEM Learning - Andriani Sariwardani (Pt. Anagata Sembagi Education, 2025)
Declining student interest in STEM learning has become a critical concern in the global education landscape. This study aims to identify school management strategies that effectively increase STEM motivation through a systematic literature review of 32 peer reviewed articles published in the last decade. The synthesis reveals that institutional school policies play a decisive role in shaping long term STEM engagement among students. Four dominant policy strategies were identified: curriculum integration and alignment, experiential learning mandates, strategic technology and resource allocation and professional development ecosystems for teachers. The effectiveness of these strategies depends on whether policies operate as coordinated and sustained management frameworks rather than fragmented classroom initiatives. The findings further indicate that sustainability requires schools to implement long term reinforcement structures that support teacher capacity, technological adaptability and equitable STEM experiences across grade levels. This study contributes to the literature by presenting an evidence based managerial framework for enhancing student interest in STEM learning. Future implementations should prioritize leadership driven institutional transformation to ensure consistent and meaningful student engagement